2003
DOI: 10.1016/s0167-2789(03)00227-6
|View full text |Cite
|
Sign up to set email alerts
|

Structure-preserving model reduction for mechanical systems

Abstract: This paper focuses on methods of constructing of reduced-order models of mechanical systems which preserve the Lagrangian structure of the original system. These methods may be used in combination with standard spatial decomposition methods, such as the Karhunen-Loève expansion, balancing, and wavelet decompositions. The model reduction procedure is implemented for three-dimensional finite-element models of elasticity, and we show that using the standard Newmark implicit integrator, significant savings are obt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
112
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 143 publications
(116 citation statements)
references
References 39 publications
2
112
0
Order By: Relevance
“…Krysl et al [6] and Lall et al [7] reported model reduction techniques in which they limited the space of possible deformations. Wojtan and Turk [3] employed an FEM representation with embedded high-resolution surface mesh.…”
Section: Related Workmentioning
confidence: 99%
“…Krysl et al [6] and Lall et al [7] reported model reduction techniques in which they limited the space of possible deformations. Wojtan and Turk [3] employed an FEM representation with embedded high-resolution surface mesh.…”
Section: Related Workmentioning
confidence: 99%
“…In mechanics, a natural way to restrict a system to a subspace is by means of constraints [26], and, from a physical viewpoint, it makes sense to study the limit of vanishing small HSVs, i.e., to gradually eliminate the least observable and controllable states, thereby forcing the system to the limiting controllable and observable subspace.…”
Section: Strong Confinement Limitmentioning
confidence: 99%
“…All of these properties can be viewed as fundamental to a model of a mechanical system. Methods for model reduction, which take account of this underlying geometry and preserve it, are developed in References [7,40]. The importance of this is evidenced in Figure 2, where each mode shape appears twice; this is a consequence of the underlying correspondence between con"guration variables and their generalized momenta.…”
Section: Empirical Balancingmentioning
confidence: 99%